Dose-effect relationship for several coagulation markers during administration of the direct thrombin inhibitor S 18326 in healthy subjects - Gaussem, P (Blackwell Science, Ltd, 2002)
AIMS: We conducted a phase I placebo-controlled trial with two i.v. doses (0.5 mg h−1 and 3 mg h−1) of S 18326, a selective thrombin inhibitor that interacts with the catalytic site of thrombin, with the aim to study the relationships between increasing plasma levels of S 18326 and changes in coagulation tests and thrombin generation markers. METHODS: Thirty-six healthy male volunteers were divided into three groups. In each group, 10 volunteers were randomly assigned to receive S 18326 and two to receive a placebo. Following a bolus of 4.5 mg, doses were 0.5 mg h−1 in the first group and 3 mg h−1 in the two other groups, administered as an i.v. infusion for 24 h. Blood was drawn repeatedly up to 36 h after the bolus, and tested for the activated clotting time (ACT) and activated partial thromboplastin time (APTT). The APTT reagent was chosen among five commercial reagents to yield a linear increase in the clotting time among possible therapeutic S 18326 concentrations in vitro. To accurately measure the thrombin-inhibiting effects of low doses of S 18326 (< 0.5 µm), we developed a specific chromogenic assay. We also measured F1 + 2 prothrombin fragment levels to assess the effect of S 18326 on thrombin generation in vivo. RESULTS: A two-compartment pharmacokinetic model was fitted to the S 18326 plasma concentration vs time data by using population pharmacokinetic methods. Results of the pharmacodynamic-pharmacokinetic relationships showed that both the ACT and APTT methods yielded a linear increase according to the S 18326 concentration measured using a highly sensitive analytical method. At the end of infusion, ACT was prolonged 1.20 and 1.95-fold in the 0.5 mg h−1 and the 3 mg h−1 groups, respectively, and APTT was prolonged 1.27 and 2.75-fold. Thrombin inhibition plateaued above 0.5 µm of S 18326 according to an Emax model, confirming that the test was highly sensitive. F1 + 2 levels fell significantly after the 24 h S 18326 infusion (0.83 nm to 0.6 nm and 0.80 nm to 0.44 nm in the 0.5 mg h−1 and the 3 mg h−1 groups, respectively), but remained stable after the placebo infusion. CONCLUSIONS: Our results support specific monitoring of the thrombin inhibitor S 18326 with ACT and APTT to establish the safety range of the drug in further studies. Moreover, the fall in F1 + 2 prothrombin fragments suggests that S 18326 effectively reduces the retroactivation of factors V and VIII by thrombin.